Efficacy and safety of dupilumab in patients with moderate-to-severe atopic dermatitis and comorbid allergic rhinitis - Tian, Tengfei; Li, Yueguang; Yuan, Guangmei; Jiang, Wenxiu (Frontiers in Medicine, 2025)
ObjectiveTo examine the efficacy and safety of dupilumab treatment in moderate-to-severe atopic dermatitis (AD) patients with comorbid allergic rhinitis (AR).MethodsA total of 26 patients received subcutaneous dupilumab every 2 weeks and were followed up for 16 weeks. The efficacy assessment was evaluated based on clinical parameters every 4 weeks, including the Eczema Area and Severity Index (EASI), Pruritus Numeric Rating Scale (P-NRS), Severity Index (EASI), and Dermatology Life Quality Scale (DLQI) for the severity of AD symptoms, and the total nasal symptom scores (TNSS), visual analogue scale (VAS) and Mini Rhino-conjunctivitis Quality of Life Questionnaire (MiniRQLQ) for the severity of AR symptoms. The serum total immunoglobulin E (IgE) and eosinophil levels were collected at baseline and 16 weeks after dupilumab treatment. Treatment-emergent adverse events (TEAEs) ware conducted to evaluate the safety profile of dupilumab.ResultsDupilumab treatment resulted in a significant improvement in AD symptoms after 16 weeks as demonstrated by reduced EASI, NRS, DLQI, and ADCT scores. In addition, dupilumab treatment had a significant improvement in AR symptoms based on reduced TNSS, VAS and MiniRQLQ scores. After 16 weeks of dupilumab treatment, the blood eosinophil count, eosinophil percentage, and total serum IgE levels were significantly decreased when compared with the baseline values (P < 0.01 both). During the treatment period, the incidence of TEAEs was 13.77% (n = 8). The most commonly reported TEAEs were injection-site reactions (n = 13, 60.25%),ConclusionDupilumab treatment resulted in clinically relevant improvements in symptoms of AD and AR and had an acceptable safety profile.